STRATEGIC MANAGEMENT ACCOUNTING, DIGITALIZATION OF ACCOUNTING PRACTICES AND PERFORMANCE AMONG CONSUMER GOODS FIRMS IN LAGOS STATE - Yusuf Alabi Olumoh (Malete Journal of Accounting and Finance)
Modern management accounting practices have posed challenges for global manufacturing companies, particularly in the transition from traditional to strategic methods. This transition has been notably deficient among numerous consumer goods firms in Nigeria, where the absence of effective strategic costing practices has led to significant issues such as cost inefficiency, competitive disadvantage, and ineffective decision-making. Recognizing the significance of technological advancement for growth and competitiveness, this study investigated the impact of strategic management accounting and digitalization of accounting practices on the performance of consumer goods companies in Lagos. The research methodology employed a survey research design, sampling 161 management employees from 45 consumer goods companies in Lagos as of January 2023. The research utilized partial least square structural equation modelling to analyse primary data. Results highlighted significant impacts on Consumer goods performance from strategic costing practices and the digitalization of accounting methods. Both strategic costing practices and digitalization displayed positive and noteworthy effects on performance, reflected by t-values of 0.213 and 0.218, along with respective p-values of 0.037 and 0.023. However, strategic customer accounting practices exhibited an insignificant impact on performance, evident through a t-value of 1.345 and a p-value of 0.179 at a 5% significance level. The study concludes that strategic costing and digitalizing accounting methods highly influence and benefit and consumer goods firms’ performance, unlike strategic customer accounting. The study recommends that the implementation and integration of effective strategic costing methodologies and digitalization initiatives to further propel the growth and competitiveness of these companies in Lagos State